Regeneration of Al-Qur'an Love Education Realized Through Tahfidz Extracurricular Education - Nur Zaytun Hasanah; Syaifulloh Yusuf; Istiqomah ,; Hafizh Alim Ibnu Fatahillah (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2022)
Talking about Indonesia will never end. Lately, many generations of students are far from Islam. It does not matter if Allah is pleased or not. Even the Qur’an was ignored. Education is not just looking for grades on a diploma, but education is a place to seek knowledge, then implement the knowledge gained in everyday life, and after that pass it on to others. The purpose this article is to interpret the regeneration of Al-Qur’an love education realized through the extracurricular tahfidz MTS N 2 Sleman. This research is a type of qualitative research with a qualitative descriptive research approach. The data analysis technique used is by Miles, Huberman, and Saldana with the stages of data collection, data condensation, data presentation and conclusion drawing. The results showed that the tahfidz extracurricular activities at MTS N 2 Sleman were able to restore the generation of Al-Qur’an love education as evidenced by the students participating in tahfidz extracurricular activities twice a week. Thus, the love of the Qur’an education desired by the creator will be able to output generations that are useful for the future of the Indonesian nation.